Penerapan Model Pembelajaran Picture and Picture Dalam Meningkatkan Hasil Belajar PKn - Nurhilal Nurhilal (JURNAL GLOBAL EDUKASI, 2017)
Abstract: This study aims to remind the learning outcomes of Civics in the material of Village Government System by applying the model of learning Picture and Picture. Subjects in this study were the fourth grade students of SD Negeri 010076 Pondok Bungur district Rawang Panca Arga academic year 2016/2017 amounted to 25 people. The results of the learning process before the study through the model of learning Picture and Picture reached an average value of 53.04. After being motivated, the research through cycle I and cycle II of reflection and recommendation of average score reached 87.64. Learning outcomes in the first cycle reached the value of classical learning completeness of 77.88% after reflection and recommendations in cycle II completeness of classical learning reached 100%. Can be concluded with the application of learning model Picture and Picture can remind the learning result of Civics on the material of Village Government System of fourth grade students of SD Negeri 010076 Pondok Bungur district Rawang Panca Arga academic year 2016/2017. Keywords: picture and picture, village government system Abstrak: Penelitian ini bertujuan untuk meningatkan hasil belajar PKn pada materi Sistem Pemerintahan Desa dengan menerapkan model pembelajaran Picture and Picture. Subjek dalam penelitian ini adalah siswa kelas IV SD Negeri 010076 Pondok Bungur kec. Rawang Panca Arga TP. 2016/2017 berjumlah 25 orang. Hasil proses belajar sebelum penelitian melalui model pembelajaran Picture and Picture mencapai nilai rata-rata 53,04. Setelah termotivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 87,64. Hasil belajar pada siklus I mencapai nilai ketuntasan belajar klasikal sebesar 77,88% setelah refleksi dan rekomendasi pada siklus II ketuntasan belajar klasikal mencapai 100%. Dapat disimpulkan dengan penerapan model pembelajaran Picture and Picture dapat meningatkan hasil belajar PKn pada materi Sistem Pemerintahan Desa siswa kelas IV SD Negeri 010076 Pondok Bungur kec. Rawang Panca Arga TP. 2016/2017. Kata kunci: picture and picture, sistem pemerintahan desa